Authigenic carbonates from an active cold seep of the northern South China Sea: New insights into fluid sources and past seepage activity - Feng, Dong; Chen, Duofu (Deep-sea research. Part II, Topical studies in oceanography, 2015)
Site F (also named Formosa ridge) represents the most vigorous cold seep on the northern South China Sea continental slope. In order to constrain the fluid sources and intensities of seepage, we investigated the petrography, mineralogy, stable carbon and oxygen isotopic compositions, element geochemistry and radiocarbon dating of authigenic carbonate rocks retrieved from the seafloor. Carbonate rocks mainly occurred as crusts, nodules, and nodular masses incorporated in carbonate breccias. The carbonates were comprised mainly of high-Mg calcite and aragonite. The δ13C of authigenic carbonate varied from −55.3‰ to −34.3‰ (mean: −48.5‰; n=47) vs. V-PDB, suggesting biogenic methane is the dominant carbon source fuelling the system. The δ18OCarbonate values were from +3.6‰ to +4.8‰ (mean: +3.9‰; n=47). The observed 18O-enrichement in relation to calculated equilibrium values in the carbonates probably reflects dissolution of gas hydrates. Combination of seafloor observations and the obtained AMS 14C ages suggest that (1) initiation of methane seepage from at least 10.6ka ago; (2) environmental conditions may have been favorable for enhanced fluid seepage around 6ka BP and (3) relatively low intensity of seepage from 2ka BP till today. •Biogenic methane is the primary carbon source of seep carbonates at Site F.•Anomalously positive δ18O values of seep carbonates reflect dissociation of gas hydrate.•Authigenic carbonates are good recorder of fluid dynamics at cold seeps.•Seafloor observations and radiocarbon dating suggest changing fluid flow at seeps.